671 The Effect of Supplementary Simulation-Based Procedural Training: The SIMULATE Randomised Controlled Clinical and Educational Trial. (19th August 2022) - Aydin, Abdullatif; Ahmed, Kamran; Raison, Nicholas; Abe, Takashige; Brunckhorst, Oliver; Van Hemelrijck, Mieke; Ahmed, Hashim; Shinohara, Nobuo; Zhu, Wei; Zeng, Guohua; Sfakianos, John; Tewari, Ashutosh; et al.
Abstract: Aim: To evaluate whether surgical trainees undergoing additional simulation, compared to conventional training, are able to achieve proficiency sooner with better patient outcomes. Methods: This international, multicentre randomised controlled superiority trial recruited urology trainees (n=94) who had performed ≤10 ureterorenoscopy (URS) cases, as a selected index procedure, with no prior simulation experience. Recruits were randomised to simulation-based training or non-simulation-based training groups, the latter of which is the current standard of training. Training sessions were conducted for the simulation arm, utilising an expert-developed multi-modality training curriculum. The primary outcome was the number of procedures required to achieve proficiency, defined as achieving a score of ≥28 on an OSATS scale, on 3 consecutive operations, without complications. Inpatient surgical complications were also recorded. All participants were followed up for 25 procedures or over 18 months. Results: A total of 1140 cases were performed by 65 participants where proficiency was achieved in 21 simulation and 18 conventional participants over a median of 8 and 9 procedures, respectively (HR: 1.41 [95% CI 0.72–2.75]). More participants reached proficiency in the simulation arm in flexible ureterorenoscopy, requiring fewer number of procedures (HR 0.89 [95% CI 0.39–2.02]). Significant differences were observed in overall comparison of OSATS scores between groups (mean difference 1.42 [95% CI 0.91–1.92]; p<0.001), with fewer total complications (15 vs 37; p=0.003) and ureteric injuries (3 vs 9; p<0.001) in the simulation group. Conclusions: Simulation-based training demonstrated higher overall proficiency and fewer procedures were required to achieve proficiency in the complex form of the index procedure with surgical complications.